CD103+ CD8 T Cells in the Toxoplasma-Infected Brain Exhibit a Tissue-Resident Memory Transcriptional Profile - Landrith, Tyler A.; Sureshchandra, Suhas; Rivera, Andrea; Jang, Jessica C.; Rais, Maham; Nair, Meera G.; Messaoudi, Ilhem; Wilson, Emma H. (Frontiers in Immunology, 2017)
During chronic infection, memory T cells acquire a unique phenotype and become dependent on different survival signals than those needed for memory T cells generated during an acute infection. The distinction between the role of effector and memory T cells in an environment of persistent antigen remains unclear. Here, in the context of chronic Toxoplasma gondii infection, we demonstrate that a population of CD8 T cells exhibiting a tissue-resident memory (TRM) phenotype accumulates within the brain. We show that this population is distributed throughout the brain in both parenchymal and extraparenchymal spaces. Furthermore, this population is transcriptionally distinct and exhibits a transcriptional signature consistent with the TRM observed in acute viral infections. Finally, we establish that the CD103+ TRM population has an intrinsic capacity to produce both IFN-γ and TNF-α, cytokines critical for parasite control within the central nervous system (CNS). The contribution of this population to pro-inflammatory cytokine production suggests an important role for TRM in protective and ongoing immune responses in the infected CNS. Accession number: GSE95105